Amauroderma niger - a New Root-rot Pathogen of Dalbergia sissoo from India - Harsh, N. S. K.; Chandra, Suresh; Pandey, Amit (Indian Forester, 2004)
A new root-rot disease of Dalbergia sissoo caused by Amauroderma niger has been studied in detail. The pathogen has been described as a new record for India along with cultural characters. The pathogenicity has been established through artificial inoculation. The disease spreads from tree to tree through root contact.